2019
DOI: 10.32725/jab.2018.006
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds of biofluids for detecting lung cancer by an electronic nose based on artificial neural network

Abstract: Lung cancer (LC) incidence represents 11.5% of all new cancers, resulting in 1.72 million deaths worldwide in 2015. With the aim to investigate the capability of the electronic nose (e-nose) technology for detecting and differentiating complex mixtures of volatile organic compounds in biofluids ex-vivo, we enrolled 50 patients with suspected LC and 50 matching controls. Tissue biopsy was taken from suspicious lung mass for histopathological evaluation and blood, exhaled breath, and urine samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Whether an eNose can differentiate lung cancer patients from healthy controls, patients with benign lung nodules or (former) smokers, has been investigated in different cohorts. All studies in (non-) small cell lung cancer ((N)SCLC) showed significant results, albeit with a wide range in reported sensitivity (71–99%) and specificity (13–100%) [ 68 80 ]. Smoking status of participants did not seem to influence accuracy of an eNose for detecting cancer [ 77 ].…”
Section: Current Clinical Applicationmentioning
confidence: 99%
“…Whether an eNose can differentiate lung cancer patients from healthy controls, patients with benign lung nodules or (former) smokers, has been investigated in different cohorts. All studies in (non-) small cell lung cancer ((N)SCLC) showed significant results, albeit with a wide range in reported sensitivity (71–99%) and specificity (13–100%) [ 68 80 ]. Smoking status of participants did not seem to influence accuracy of an eNose for detecting cancer [ 77 ].…”
Section: Current Clinical Applicationmentioning
confidence: 99%
“…The measured results consisted of vectors of 64 values every 20 s for each of the three sensors. Previous studies, with varying degrees of success, have used the “electronic nose” device to diagnose lung [ 15 , 17 , 25 , 26 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], colon [ 36 , 37 ], head and neck [ 34 , 37 , 38 ], urinary bladder [ 37 ], prostate [ 39 ], stomach [ 28 ] and breast cancer [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…were extracted and further analysed, as we detailed earlier. [13][14][15] Sensor Name Reference Substance Ontario, Canada). The air was drawn from the top of blood samples using a syringe then dissolved in 10 ml of Alpha-Q purified water (Millipore, Bedford, MA, USA), which acted as a solvent in a volumetric flask.…”
Section: Electronic Nose (E-nose)mentioning
confidence: 99%
“…12 Moreover, the recent availability of highly sensitive and portable technologies like Electronic Nose (E-Nose) has provided necessary tools for detecting disease-specific VOCs in clinical matrices quickly and cheaply. [13][14][15] An E-Nose is an artificial gas-sensing system consisting of an array of non-specific chemical sensors of variable numbers, usually between 10 and 32, capable of detecting and classifying VOCs using pattern recognition algorithms. 14 However, E-Noses can only qualitatively detect complex odour mixtures of VOCs associated with various diseases without identifying individual chemical species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation